InteIrcultural Competence Development for International Business Environment - Garazi Azanza Martínez de Luco; José Antonio Campos Granados; Paulina Mizerska; Remigiusz Mazur (Edukacja Ustawiczna Dorosłych)
The article presents the results of the work that has been carried out by an international team of partners from Poland, Italy, Spain, and Turkey as part of the Erasmus+ project entitled Interculturality – Intercultural Competence Development for International Business Environment. The project aimed to develop materials enabling educators to improve intercultural competences of adults by means of a training program and Continuing Professional Development course which are offered as open educational resources. Main issues and areas that constitute intercultural competences, important for people working in the international environment, were identified on the basis of scientific literature analysis. The final results of the project were achieved through the examination of training courses dedicated to developing intercultural competences that are available on the European market, consultations with representatives of international enterprises, gaps identification, preparation of the training program as well as pilot testing of the developed materials. Project results and the work that has been done in the transnational partnership of the Erasmus+ project highlight the importance of developing intercultural competences in the context of managing multicultural organisations.